Errors analysis of Malay compound sentences of foreign language learners - Johari, Arina; Abdul Latiff@Bapoo, Lili Suriani; Wahab Abdul Rahman, Shahrizal Idzuan (IDOSI Publications, 2014)
This study analyzed the essays written by 41 learners of Malay as a foreign language at the International Islamic University Malaysia and reports the errors found in the compound sentences constructed in the language. It was found that the learners had problems in using the correct spellings, punctuations, conjunctions, verb forms, vocabulary and sentence structures. It is suggested that more drillings, practices and exposures to the language are given to learners of Malay so that their grammar can be improved. Student-centred approaches may also be helpful in improving their level of proficiency. Key words: Error Compound sentences Malay Language learners